Evaluation of Subway Emergency Evacuation Based on Combined Theoretical and Simulation Methods - Yang Hui; Shujie Su; Hui Peng (Applied Sciences)
In this paper, a thorough investigation of the emergency evacuation capabilities of subway systems has been undertaken, employing a blend of theoretical models and simulation methodologies. Initially, a theoretical framework was established to estimate the evacuation duration for passengers transitioning from the train to a secure area while considering the spatial configuration and passenger flow dynamics of subway stations. Following this, a real-time visualization simulation model was developed, which integrates the dynamic aspects of passenger flow and the transportation capacity of evacuation bottlenecks across various segments. This model incorporates both spatial parameters and the travel behaviors of passengers. Ultimately, in accordance with actual operational needs, a simulation analysis was performed for substantial passenger volumes across three representative scenarios to assess the effectiveness and scientific validity of the theoretical calculation model. This study offers a foundational framework for the management of subway safety operations, facilitating the identification of evacuation bottlenecks and the implementation of emergency strategies for handling large passenger flows.